Income Inequality in Small States and the Caribbean : Stylized Facts and Determinants. (IMF Working Papers; Working Paper ;, 2021)
Rising income inequality has emerged as a major policy issue facing policymakers, but there is a dearth of empirical work on inequality in small states, including the Caribbean. Despite data limitations, the empirical analysis using a sample of small states finds that increased openness and deeper economic integration including financial market openness is associated with lower income inequality, whereas elevated debt levels limit fiscal space and are associated with higher income inequality. An important policy implication is that well targeted social sector spending aimed at improving education and health indicators will support increased redistribution and reduce income inequality.